2012
DOI: 10.7314/apjcp.2012.13.12.5955
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Hepatocellular Carcinoma in Asia

Abstract: Hepatocellular carcinoma (HCC), the sixth most prevalent cancer worldwide, continues to have high prevalence example in China. HBV vaccination should be the major preventive tactic in Asian countries. The burden of HCC is low in Iran because most cases are due to HBV and this infection was less common. Although in Iran, a mass vaccination program started in 1993, its impact on decreasing the burden of HCC due to HBV can only be expected in future decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Hepatocelluar carcinoma (HCC), the sixth most prevalent cancer type, ranks the third leading cause of cancer-related mortality worldwide (Forner et al, 2012), especially in many countries of Asia (Fazeli et al, 2012). Although surgical resection is considered to be the most effective therapeutic method for treatment of patients with primary hepatic carcinoma, the high recurrence rate and early distant metastasis of HCC after surgery remains frustrating (Kobayashi et al, 2006;Tralhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocelluar carcinoma (HCC), the sixth most prevalent cancer type, ranks the third leading cause of cancer-related mortality worldwide (Forner et al, 2012), especially in many countries of Asia (Fazeli et al, 2012). Although surgical resection is considered to be the most effective therapeutic method for treatment of patients with primary hepatic carcinoma, the high recurrence rate and early distant metastasis of HCC after surgery remains frustrating (Kobayashi et al, 2006;Tralhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Poorly differentiated OSCC has been observed in the tongue, floor of the mouth, and palate, while Rai and Ahmed's study in Karnataka found examples of well-differentiating OSCC in the buccal mucosa, the area most frequently damaged by tobacco use and followed by the tongue (2016). The larynx (36%) and pharynx (28.5%), however, are the two regions most frequently affected by head and neck cancer, according to a different study (Fazeli et al 2011). Regional variances, exposure to various risk factors, and lifestyles in various parts of the world may all contribute to this observational discrepancy (Fazeli et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, hepatitis B or C viruses (HBV/HCV) are risk factors for around 80% of HCC cases [37]. In Iran, 80% of cases of developed HCC type are positive for at least one of the HBV markers; this virus seems to be the most frequent cause of HCC in Iran [38]. Since most cases of HCC are due to HBV and this infection was lower common in Iran, the burden of HCC type is low in this country [38].…”
Section: Resultsmentioning
confidence: 99%